An Isogeometric Analysis Approach to Kinematics of Spatial Rigid Multibody Systems with Imperfect Joints - Remzija Cerimagic; Lisbeth Fajstrup; Torben Ole Andersen; Per Johansen (Modeling, Identification and Control, 2020)
This paper proposes a novel generic methodology for kinematics of spatial rigid-multibody systems with and without lubricated joints. In this method CAD surface representations in the form of non-uniform rational B-splines (NURBS) are used to address the interface kinematics. This eliminates the time and effort needed to manually parameterize the interface geometry, by enabling a direct use of the engineering designs encapsulated in CAD systems. Furthermore, the use of NURBS for surface representation allows integration of tribodynamics into an isogeometric analysis (IGA) setting. The kinematic formulation is based on a new implicit matrix approach for implicitization of CAD surfaces in three-dimensional space. The construction of such implicit matrices and their properties are explained, and explicit expressions for the gap height distance, velocity and relative velocities in a general clearance joint are provided.